2011
DOI: 10.2478/v10077-011-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubular Titanium Oxide Layers for Enhancement of Bone-Implant Bonding and Bioactivity

Abstract: Titanium and titanium alloys are frequently used in orthopaedic implants in load bearing situations because they possess favourable properties, such as a good ductility, tensile and fatigue strength, modulus of elasticity matching that of bones, low weight, and good biocompatibility. The drawback of Ti implants is their poor osseointegration and osteoconductive properties. The present paper describes the techniques to improve the bioactivity of titanium and enhance the bone-implant bonding ability by the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This is also the case in biological systems, where a bioliquid surrounds the metal [ 13 , 14 , 15 , 16 , 17 ]. In the case of implants, the stoichiometric defects and low stability of this film can lead to their delamination and loosening [ 18 , 19 , 20 ]. Therefore, it becomes necessary to make the biocompatible coating permanently bond with the surface of implants.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case in biological systems, where a bioliquid surrounds the metal [ 13 , 14 , 15 , 16 , 17 ]. In the case of implants, the stoichiometric defects and low stability of this film can lead to their delamination and loosening [ 18 , 19 , 20 ]. Therefore, it becomes necessary to make the biocompatible coating permanently bond with the surface of implants.…”
Section: Introductionmentioning
confidence: 99%
“…It might be discussed whether the oxide structure with long tubes may be susceptible to imposed stresses. This problem was considered early based on the Finite Elements Method (FEM) and a simple model of nanotubular structure [68]. It was shown that for a load imposed on the upper surface of nanotubes, being the sum of a specific structure weight and additional load ranging between 0 and 150 μN for a single nanotube, the von Mises stresses changed between 46 MPa and 1.61 GPa, and deformation between 0.19 and 17.9 nm.…”
Section: Discussionmentioning
confidence: 99%
“…26 Besides anti-inflammatory activity, 27 these systems have also shown several advantages in orthopedic applications such as improved biological activity in terms of osteoblasts attachment, proliferation, and differentiation. 28,29 Although the utilization of anti-inflammatory drug-eluting implants has shown some significant improvements, most of them are still in early research stage.…”
Section: Introductionmentioning
confidence: 99%